Representation of the Past and Public History: Women’s History on the Internet (Tempo e Argumento, 2017)
This article aims to approach the relations betweenthe internet, representation of the past, and publichistory. To do this, it resorts to analyzing thewebsite and the Facebook page “As Mina naHistória” [“Chicks in History”], created in June 2015.In this examination, it explores issues such as thetype of representation of the past provided in thisvirtual space, the profile of its audience, and thelanguage used. In order to move forward in theseissues, brief comments are made about the teachingof women’s history in Brazil. Finally, we seek,through this approach, to propose some reflectionsabout the public history that has been practiced inthe country, beyond the issue of enlargement of theaudience ‘consuming’ history.Keywords: Representation; Public History; Internet;Women.